2014
DOI: 10.1089/ars.2013.5361
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase Mimic Ebselen Improves Glucose-Stimulated Insulin Secretion in Murine Islets

Abstract: Aims: Glutathione peroxidase (GPX) mimic ebselen and superoxide dismutase (SOD) mimic copper diisopropylsalicylate (CuDIPs) were used to rescue impaired glucose-stimulated insulin secretion (GSIS) in islets of GPX1 and(or) SOD1-knockout mice. Results: Ebselen improved GSIS in islets of all four tested genotypes. The rescue in the GPX1 knockout resulted from a coordinated transcriptional regulation of four key GSIS regulators and was mediated by the peroxisome proliferator-activated receptor gamma coactivator 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 75 publications
2
29
0
Order By: Relevance
“…However, ebselen treatment did not affect TLR4 expression, suggesting that ebselen may inhibit H. pylori LPS-induced ROS production via GPX2/4 expression as opposed to TLR4 signaling. This may be due to the fact that ebselen acts as an oxidant at redox-modulatory sites, which mimics the activity of endogenous GPX, therefore partially restores GPX antioxidant capacity (20,21). Furthermore, the present study demonstrated that phosphorylation of p38 MAPK was significantly increased following H. pylori LPS treatment and that LPS-induced phosphorylation of p38 MAPK was inhibited by treatment with ebselen.…”
Section: Discussionsupporting
confidence: 48%
“…However, ebselen treatment did not affect TLR4 expression, suggesting that ebselen may inhibit H. pylori LPS-induced ROS production via GPX2/4 expression as opposed to TLR4 signaling. This may be due to the fact that ebselen acts as an oxidant at redox-modulatory sites, which mimics the activity of endogenous GPX, therefore partially restores GPX antioxidant capacity (20,21). Furthermore, the present study demonstrated that phosphorylation of p38 MAPK was significantly increased following H. pylori LPS treatment and that LPS-induced phosphorylation of p38 MAPK was inhibited by treatment with ebselen.…”
Section: Discussionsupporting
confidence: 48%
“…Dietary Se deficiency and(or) diet restriction partially alleviated the negative impacts of GPX1 overexpression on lipid and glucose metabolism in male mice [184,185]. In contrast, the GPX mimetic could restore partially the impaired glucose-stimulated insulin secretion and related signaling in the GPX1 −/− mice [186].…”
Section: Glutathione Peroxidases (Gpxs)mentioning
confidence: 94%
“…Thus, hepatic GPx1 may prevent hepatic steatosis indirectly by regulating ROS levels. Further supporting the protective function of GPx1, the GPx mimetic, ebselen, was found to restore islet function in GPx1-/- mice through a PGC-1α dependent mechanism [ 82 ]. Nrf2 is a transcription factor that controls the transcription of antioxidant enzymes by interacting with an antioxidant response element (ARE).…”
Section: Selenoproteins In Metabolic Diseasementioning
confidence: 99%